1. Ta có: \(\left(x-y\right)^2-\left(x+y\right)^2=\left(x-y+x+y\right)\left(x-y-x-y\right)=2x.\left(-2y\right)=-4xy\)
2. Ta có: \(\left(7n-2\right)^2-\left(2n-7\right)^2=\left(7n-2-2n+7\right)\left(7n-2+2n-7\right)=\left(5n+5\right)\left(9n-9\right)=9\left(n-1\right)\left(5n+5\right)\)
\(\Rightarrow\left(7n-2\right)^2-\left(2n-7\right)^2\) chia hết cho 9 với mọi giá trị nguyên của n.
3. Ta có: \(F=-x^2+6x+1=-\left(x^2-6x-1\right)=-\left(x^2-6x+9-10\right)=-\left(x-3\right)^2+10\)
Vì \(-\left(x-3\right)^2\le0\Rightarrow-\left(x-3\right)^2+10\le10\)